The Existence of Publicity Principles in Complete Systematic Land Registration - Anak Agung Istri Chintya Paramitha; I Made Suwitra; I Nyoman Alit Puspadma (NOTARIIL Jurnal Kenotariatan, 2020)
This study aims to analyse the legal certainty of land rights certificates through the complete systematic land registration program regulated in Permen ATR / BPN No.6 / 2018. The issues examined include the legal certainty of land rights certificates issued based on Permen ATR / BPN No.6 / 2018 and legal protection of certificates issued under Permen ATR / BPN No.6 / 2018 for holders of certificates of land rights. This study uses normative legal research. The data was primary and secondary legal materials related to land registration. The results of the study are associated with legal objectives, then Permen ATR / BPN No. 6/1997 provides great advantages and can create an element of justice by issuing certificates throughout the community, so that legal certainty is given but it becomes weak due to disharmony between the two rules. So that applies the legal principle of the lex superiori derogat legi inferiori. The lower provisions are null and void and have no binding legal force as a result, land rights certificates issued based on Permen ATR / BPN No.6 / 2018 do not have legal power. In order to achieve legal certainty and protection, the provisions of Article 24 paragraph (2) Permen ATR / BPN No.6 / 2018 is adjusted to Article 26 paragraph (1) PP No. 24/1997 or the rules regarding PTSL are made in laws and regulations of the same level or higher than PP No.24 / 1997.